Quality indicators for in‐hospital management of exacerbation of chronic obstructive pulmonary disease: results of an international Delphi study. (21st June 2012) - Lodewijckx, Cathy; Sermeus, Walter; Panella, Massimiliano; Deneckere, Svin; Leigheb, Fabrizio; Troosters, Thierry; Boto, Paulo Alexandre; Mendes, Rita Veloso; Decramer, Marc; Vanhaecht, Kris
<x xml:space="preserve">Abstract</x> lodewijckx c., sermeus w., panella m., deneckere s., leigheb f., troosters t., boto p.a., mendes r.v., decramer m. & vanhaecht k. (2012) Quality indicators for in‐hospital management of exacerbation of chronic obstructive pulmonary disease: results of an international Delphi study. Journal of Advanced Nursing69(2), 348–362. doi: 10.1111/j.1365‐2648.2012.06013.x Abstract Aim. To report a Delphi study that was conducted to select process and outcome indicators that are relevant to study quality of care and impact of care pathways for patients hospitalized with exacerbation of chronic obstructive pulmonary disease. Background. Management of patients hospitalized with exacerbation of chronic obstructive pulmonary disease is suboptimal and outcomes are poor. To evaluate the impact of care pathways properly, relevant indicators need to be selected. Design. Delphi study. Methods. The study was conducted over 4 months in 2008, with 35 experts out of 15 countries, including 19 medical doctors, 8 nurses and 8 physiotherapists. Participants were asked to rate, for 72 process and 21 outcome indicators, the relevance for follow‐up in care pathways for in‐hospital management of exacerbation of chronic obstructive pulmonary disease. Consensus (agreement by at least 75% of the participants) that an indicator is relevant for follow‐up was sought in two rounds. Results. Consensus was reached for 26 of 72 process indicators (36·1%) and 10 of 21 outcome indicators (47·6%). Highest consensus levels were found for the process indicators regarding oxygen therapy (100%), pulmonary rehabilitation (100%) and patient education (94·5–88·6%) and for the outcome indicators concerning understanding of therapy (91·4–85·7%) and self‐management (88·6–88·2%). Conclusion. The selected indicators appear to be sensitive for improvement. Therefore, researchers and clinicians that want to study and improve the care for patients hospitalized with exacerbation of chronic obstructive pulmonary disease should primarily focus on these indicators.